مفهوم المطابقة وجمالياتها: دراسة بلاغية تحليلية نقدية - د. وداعة عبد الله علي سرار; د. آدم محمد أبو القاسم عبد الله (White Nile Journal for Studies and Research, 2017)
The Holy Quran uses the various styles of phrase making in a unique way not found before in Arabs literature it is a miracle in its style and communiqué such as the a availability of phrasemalirs image that functioning communiquéand meaning in approximating that lead to complete under standing to the receiver The study defines the approximating idiomafrcally and conventionally The study handles the approximating and its dimensions, place and role in the Holy Quran text. Then to explain its concept in different phrasemalirsbooks It surmising various condition as: near to take for to execute and this is good and nicer Survey is better for approximating in different styles, this reveals the richness of the Holy Quran and Arabian clearness in satiate the tastes with meanings and one Noun and verb also join between two verbs rather then the hidden approximating and renominating approximatingwhich is preamble increase the speech glary and vividness the approximating comes in different ways that indicate to harmoniong between the text and status and this is missed of rhetoricians. The study has some finding as: approximating is deep roated in the Holy Quran because of its great role in revealing the rightness and wrongness and establishing the understanding in the receiver and the speech turn to be evidence either for or against and a approximating lead to achieve the accurate meaning throughout comparison between two meaning which lead to clear cat limit to the intended meaning and the beauty of the approximating hides in reaching the meaning not to the accidental saying.